Correlation between osteoarthritis grading in femoropatella joint and patella malalignment with pain and disability using WOMAC score - S Kiswati; Bantar Suntoko; H Sukmaningtyas (Indonesian Journal of Rheumatology, 2016)
Background: Osteoarthritis (OA) in femoropatella often causes pain and disabilities in the lower extremities. In 2011 found a significance association between knee pain with osteophytes in femoropatella joints compared with osteophytes in femorotibia joints. Niu J et al. found knee joint with lateral patellar malalignment and lateral patellar tilt had increased prevalence of femoropatella OA, similar study in Caucasian and African Americans patients found an association between patellar malalignment with severe knee pain and diseaseprogressivity. In this study, researchers correlate grading OA genu with pain and disability using WOMAC scores and malalignment correlate with pain and disability with WOMAC scores without assessing the progression of the disease. In this study, using cross-sectional at one time whereas previous studies using multi-center cohort were evaluated 3 to 5 years later to assess the progression of the disease. Objective of this study is to establish a correlation between OA grading in femoropatella joint and patellar malalignmentwith pain and disability using WOMAC Score.Method: Observational analytic study with crosssectional and consecutive sampling was performed in this study. In the WOMAC correlation with KellgrenLawrence grading on the WOMAC OA genu and grading narrowing between joints using the Rank Spearmanwhile the different test WOMAC with malalignment using T test Results: WOMAC OA genu of the grading (AP/LAT/Skyline) r = 0.488; p = 0.003, WOMAC OA genu of the grading (AP/LAT) r = 0.452 ; p = 0.006, WOMAC OA genu of the grading (AP/Skyline) r = 0.362 ; p = 0.033, WOMAC towards narrowing between joints gradingfemoropatella r = 0.370 ; p = 0.026, no differences between patellar malalignment with WOMAC score, with malalignment (p = 0.711) without malalignment(p = 0.751).Conclusion: In AP/LAT/Skyline, AP/LAT, AP/Skyline position and grading narrowing femoropatella joint space was found a significant positive correlation between OA knee’s grading and WOMAC score. No differences in T test between patella malalignment with pain and disability using WOMAC score.Keywords: femoropatella osteoarthritis, patellar malalignment, WOMAC score.